Using state-and-transition simulation models to scope post-fire success in restoring greater sage-grouse habitat - Elizabeth K. Orning; Julie A. Heinrichs; David A. Pyke; Peter S. Coates; Cameron L. Aldridge (Ecological Modelling, 2023)

Targeting Sagebrush (Artemisia Spp.) Restoration Following Wildfire with Greater Sage-Grouse (Centrocercus Urophasianus) Nest Selection and Survival Models - Cali L. Roth; Shawn T. O’Neil; Peter S. Coates; Mark A. Ricca; David A. Pyke; Cameron L. Aldridge; Julie A. Heinrichs; Shawn P. Espinosa; David J. Delehanty (Environmental Management, 2022)
Unprecedented conservation efforts for sagebrush ( Artemisia spp.) ecosystems across the western United States have been catalyzed by risks from escalated wildfire activity that reduces habitat for sagebrush-obligate species such as Greater Sage-Grouse ( Centrocercus urophasianus ). However, post-fire restoration is challenged by spatial variation in ecosystem processes influencing resilience to disturbance and resistance to non-native invasive species, and spatial and temporal lags between slower sagebrush recovery processes and faster demographic responses of sage-grouse to loss of important habitat. Decision-support frameworks that account for these factors can help users strategically apply restoration efforts by predicting short and long-term ecological benefits of actions. Here, we developed a framework that strategically targets burned areas for restoration actions (e.g., seeding or planting sagebrush) that have the greatest potential to positively benefit sage-grouse populations through time. Specifically, we estimated sagebrush recovery following wildfire and risk of non-native annual grass invasion under four scenarios: passive recovery, grazing exclusion, active restoration with seeding, and active restoration with seedling transplants. We then applied spatial predictions of integrated nest site selection and survival models before wildfire, immediately following wildfire, and at 30 and 50 years post-wildfire based on each restoration scenario and measured changes in habitat. Application of this framework coupled with strategic planting designs aimed at developing patches of nesting habitat may help increase operational resilience for fire-impacted sagebrush ecosystems.

Transient population dynamics impede restoration and may promote ecosystem transformation after disturbance - Robert K. Shriver; Caitlin M. Andrews; Robert S. Arkle; David M. Barnard; Michael C. Duniway; Matthew J. Germino; David S. Pilliod; David A. Pyke; Justin L. Welty; John B. Bradford (Ecology Letters, 2019)
The apparent failure of ecosystems to recover from increasingly widespread disturbance is a global concern. Despite growing focus on factors inhibiting resilience and restoration, we still know very little about how demographic and population processes influence recovery. Using inverse and forward demographic modelling of 531 post‐fire sagebrush populations across the western US, we show that demographic processes during recovery from seeds do not initially lead to population growth but rather to years of population decline, low density, and risk of extirpation after disturbance and restoration, even at sites with potential to support long‐term, stable populations. Changes in population structure, and resulting transient population dynamics, lead to a > 50% decline in population growth rate after disturbance and significant reductions in population density. Our results indicate that demographic processes influence the recovery of ecosystems from disturbance and that demographic analyses can be used by resource managers to anticipate ecological transformation risk.

Resiliency of biological soil crusts and vascular plants varies among morphogroups with disturbance intensity - Lea A. Condon; David A. Pyke (Plant and Soil, 2018)

Fire and Grazing Influence Site Resistance to Bromus tectorum Through Their Effects on Shrub, Bunchgrass and Biocrust Communities in the Great Basin (USA) - Lea A. Condon; David A. Pyke (Ecosystems, 2018)

Adapting management to a changing world: Warm temperatures, dry soil, and interannual variability limit restoration success of a dominant woody shrub in temperate drylands - Robert K. Shriver; Caitlin M. Andrews; David S. Pilliod; Robert S. Arkle; Justin L. Welty; Matthew J. Germino; Michael C. Duniway; David A. Pyke; John B. Bradford (Global Change Biology, 2018)
Restoration and rehabilitation of native vegetation in dryland ecosystems, which encompass over 40% of terrestrial ecosystems, is a common challenge that continues to grow as wildfire and biological invasions transform dryland plant communities. The difficulty in part stems from low and variable precipitation, combined with limited understanding about how weather conditions influence restoration outcomes, and increasing recognition that one‐time seeding approaches can fail if they do not occur during appropriate plant establishment conditions. The sagebrush biome, which once covered over 620,000 km 2 of western North America, is a prime example of a pressing dryland restoration challenge for which restoration success has been variable. We analyzed field data on Artemisia tridentata (big sagebrush) restoration collected at 771 plots in 177 wildfire sites across its western range, and used process‐based ecohydrological modeling to identify factors leading to its establishment. Our results indicate big sagebrush occurrence is most strongly associated with relatively cool temperatures and wet soils in the first spring after seeding. In particular, the amount of winter snowpack, but not total precipitation, helped explain the availability of spring soil moisture and restoration success. We also find considerable interannual variability in the probability of sagebrush establishment. Adaptive management strategies that target seeding during cool, wet years or mitigate effects of variability through repeated seeding may improve the likelihood of successful restoration in dryland ecosystems. Given consistent projections of increasing temperatures, declining snowpack, and increasing weather variability throughout midlatitude drylands, weather‐centric adaptive management approaches to restoration will be increasingly important for dryland restoration success.

Fungal and bacterial contributions to nitrogen cycling in cheatgrass-invaded and uninvaded native sagebrush soils of the western USA - Nicole M. DeCrappeo; Elizabeth J. DeLorenze; Andrew T. Giguere; David A. Pyke; Peter J. Bottomley (Plant and Soil, 2017)

Climate change‐induced vegetation shifts lead to more ecological droughts despite projected rainfall increases in many global temperate drylands - Britta Tietjen; Daniel R. Schlaepfer; John B. Bradford; William K. Lauenroth; Sonia A. Hall; Michael C. Duniway; Tamara Hochstrasser; Gensuo Jia; Seth M. Munson; David A. Pyke; Scott D. Wilson (Global Change Biology, 2017)
Drylands occur worldwide and are particularly vulnerable to climate change because dryland ecosystems depend directly on soil water availability that may become increasingly limited as temperatures rise. Climate change will both directly impact soil water availability and change plant biomass, with resulting indirect feedbacks on soil moisture. Thus, the net impact of direct and indirect climate change effects on soil moisture requires better understanding. We used the ecohydrological simulation model SOILWAT at sites from temperate dryland ecosystems around the globe to disentangle the contributions of direct climate change effects and of additional indirect, climate change‐induced changes in vegetation on soil water availability. We simulated current and future climate conditions projected by 16 GCM s under RCP 4.5 and RCP 8.5 for the end of the century. We determined shifts in water availability due to climate change alone and due to combined changes of climate and the growth form and biomass of vegetation. Vegetation change will mostly exacerbate low soil water availability in regions already expected to suffer from negative direct impacts of climate change (with the two RCP scenarios giving us qualitatively similar effects). By contrast, in regions that will likely experience increased water availability due to climate change alone, vegetation changes will counteract these increases due to increased water losses by interception. In only a small minority of locations, climate change‐induced vegetation changes may lead to a net increase in water availability. These results suggest that changes in vegetation in response to climate change may exacerbate drought conditions and may dampen the effects of increased precipitation, that is, leading to more ecological droughts despite higher precipitation in some regions. Our results underscore the value of considering indirect effects of climate change on vegetation when assessing future soil moisture conditions in water‐limited ecosystems.

Resilience to Stress and Disturbance, and Resistance to Bromus tectorum L. Invasion in Cold Desert Shrublands of Western North America - Jeanne C. Chambers; Bethany A. Bradley; Cynthia S. Brown; Carla D’Antonio; Matthew J. Germino; James B. Grace; Stuart P. Hardegree; Richard F. Miller; David A. Pyke (Ecosystems, 2014)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Nitrogen limitation, 15N tracer retention, and growth response in intact and Bromus tectorum-invaded Artemisia tridentata ssp. wyomingensis communities - Dana L. Witwicki; Paul S. Doescher; David A. Pyke; Nicole M. DeCrappeo; Steven S. Perakis (Oecologia, 2013)

Effects of resource availability and propagule supply on native species recruitment in sagebrush ecosystems invaded by Bromus tectorum - Mónica B. Mazzola; Jeanne C. Chambers; Robert R. Blank; David A. Pyke; Eugene W. Schupp; Kimberly G. Allcock; Paul S. Doescher; Robert S. Nowak (Biological Invasions, 2011)

Available nitrogen: A time-based study of manipulated resource islands - Michelle M. Stubbs; David A. Pyke (Plant and Soil, 2005)